(untitled) (Itinera, 2021)
This paper aims to investigate the aesthetic implications of a particular type of image: Benjamin’s Dialectic of Stillness, whose most typical application concerns the Baroque Allegory in The Origin of German Tragic Drama. The close relations with the works of Marcel Proust are established by Benjamin himself. The minute freed from the order of time, the Instant in Proust, the extra-temporal moment in Benjamin, are the places of realization of the sublime, ready to dialectically reveal the mortal dissolution of the subject. Through the analysis of several passages from the Recherche, in the light of Benjamin’s gnoseological premises, can we say the silent misunderstanding of sublime is, like death, accessible only for a moment?